The Effective Role of BPSK in Resolving Consumer Disputes in Accordance with UUPK: Legal and Theoretical Perspectives - Udjan, Bernadeth Gisela Lema; Hermawan, Ariyanto (Sultan Jurisprudence: Jurnal Riset Ilmu Hukum, 2024)
The Supreme Court of the Republic of Indonesia (MARI) canceled the decision issued by BPSK, this shows that the legal regulation regarding BPSK, especially the Consumer Protection Law (UUPK) is not firm in providing a rule in resolving consumer disputes. The research aims to critically analyze the role of BPSK in resolving consumer disputes in terms of the theory of legislation based on the UUPK. The type of research conducted in this study is juridical-normative by examining library materials or secondary data. In order to analyze the research to be conducted and answer the formulation of the problem, the author takes a case approach that shows the incompatibility of the rules regarding BPSK. The results of this research show that there are discrepancies in UUPK in regulating BPSK. In the UUPK, it has been emphasized that BPSK's decision is final and binding so that no objection can be filed to the District Court. Not only that, BPSK is seen as a quasi-court institution, which means that BPSK's position is equal to that of a general court. This can be seen from the duties and authorities that have been regulated in the legislation. The results of this research are expected to serve as a reference or guideline as well as to contribute to the government on the UUPK in affirming a legislation to resolve consumer disputes through BPSK so that the role of BPSK becomes more important.